Reconstruction of Women’s Fiqh: An Analysis of Muhammad Shahrūr’s Contemporary Reading in a Hermeneutic Perspective - Wathani, Syamsul; Ismail, Habib; Mughzi Abdillah, Akhmad (Journal of Islamic Law, 2022)
The discourse of women’s fiqh (Islamic jurisprudence) on gender issues is still confined to authoritarianism and classical fiqh hegemony, which ignores the existence and changes in contemporary reality. Several contemporary Muslim scholars have responded and attempted to reconstruct the women’s fiqh, including Muhamamd Shahrūr. This article aims to analyze the methodological thinking of Shahrūr’s women’s fiqh in the agency of criticism of fiqh exclusivism and the reconstruction of women’s fiqh into a more comprehensive formulation of fiqh that is under social reality. This article is a literature study using the method of philosophical-hermeneutic analysis and made two of his works, Al-Kitāb wa al-Qur’an: Qirā’ah Mu’āshirah and Nahwa Ushūl Jadīdah li Fiqh al-Islamī: Fiqh al-Mar’ah, as primary data. The writers found that Shahrūr carried a contemporary reading (qirā’ah al-mu’āshirah) by making objective reality (al-wāqī’) the basis for reconstruction in his first work. In his second work, Shahrūr criticizes the mainstream view of Islamic exclusivism in laws relating to women. Based on his two works, the authors argue that the interpretation of contemporary women’s fiqh must be based on reality (rather than texts), scientific and technological advancements, a reconstructive attitude that gives a larger portion of reason and reality, and a new category of the logic of discovery.